Does the presence of grassy strips and landscape grain affect the spatial distribution of aphids and their carabid predators?. (29th August 2012) - Al Hassan, Diab; Georgelin, Ewen; Delattre, Thomas; Burel, Françoise; Plantegenest, Manuel; Kindlmann, Pavel; Butet, Alain
Abstract : 1 We investigated, over the course of 2 years, the spatial distribution and abundance of two species of aphid, Metopolophium dirhodum and Sitobion avenae, and predatory species of carabid. This was undertaken in 24 wheat fields in 'coarse‐grain' and 'fine‐grain' landscapes in western France. A greater percentage of the latter landscape was covered by hedgerows and grassland and the total area covered by fields and the average size of the fields were smaller. 2 The effects on aphid abundance of the distance from field margins, the presence of grassy strips and carabid abundance were determined in both landscapes. 3 Both aphid species were more abundant in the 'fine‐grain' landscape, which may have been a result of the higher density of semi‐natural elements. In both types of landscape, the total numbers of aphids were negatively correlated with the distance from the field margin. This may have been because aphids were dispersing from overwintering sites in field margins. The abundance of M. dirhodum was strongly negatively correlated with the presence of grassy strips in the 'coarse‐grain' landscape, although there were no such significant correlations for either of the aphid species in the 'fine‐grain' landscape. 4 Aphid and carabid abundances were negatively correlated in the 'fine‐grain' and positively in 'coarse‐grain' landscape. 5 The results obtained in the present study emphasize the importance of semi‐natural areas in agricultural landscapes in shaping the spatial distribution of aphids and carabid beetles, their natural enemies, at different spatial scales.